2013
DOI: 10.1177/0954410013475954
|View full text |Cite
|
Sign up to set email alerts
|

Experimental-numerical investigation of a pitching airfoil in deep dynamic stall

Abstract: The results of a comprehensive experimental campaign are compared to computational fluid dynamics simulations results to assess the modelling capabilities for a NACA 23012 pitching airfoil in deep dynamic stall regime. The experimental campaign involved fast unsteady pressure measurements and particle image velocimetry. Two-dimensional simulations were carried out with EDGE, developed by FOI. The investigated test case consists in a sinusoidal pitching motion with a 10 amplitude and a reduced frequency of 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In particular, the bulk velocity defect observed in the deep dynamic stall curve from 12 ∘ < < 18 ∘ in downstroke demonstrates that the flow is quite three dimensional in this range of angles of attack. The results of the threedimensional numerical simulations reported in Zanotti et al [24,25] carried out for the tested deep dynamic stall condition support this consideration. On the other hand, the quite flat behavior of the bulk velocity observed for the tested light dynamic stall condition suggests that in this regime three-dimensional flow effects are negligible during the whole pitching cycle.…”
Section: Resultssupporting
confidence: 61%
“…In particular, the bulk velocity defect observed in the deep dynamic stall curve from 12 ∘ < < 18 ∘ in downstroke demonstrates that the flow is quite three dimensional in this range of angles of attack. The results of the threedimensional numerical simulations reported in Zanotti et al [24,25] carried out for the tested deep dynamic stall condition support this consideration. On the other hand, the quite flat behavior of the bulk velocity observed for the tested light dynamic stall condition suggests that in this regime three-dimensional flow effects are negligible during the whole pitching cycle.…”
Section: Resultssupporting
confidence: 61%
“…Small discrepancies between the pitching moment curves can be observed just in the range between 16 5 5 18 in downstroke. In fact, the flow field in this incidence range is characterised by severe unsteadiness, as it was shown in the works by Zanotti and Gibertini 15 and Zanotti et al 16 Figures 7 and 8 show the comparison of the lift and quarter chord moment coefficients evaluated with the L-shaped tab deployed and retracted with respect to the clean airfoil configuration. The standard deviation of the airloads coefficients is plotted on all the airloads coefficients curves.…”
Section: Resultsmentioning
confidence: 86%
“…16,31 Thus, the flow fields presented in Figure 15 have to be taken in account just for giving an indication about the local effects introduced by the L-shaped tab, as they represent planar cuts through a strongly 3D flow field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also reported the transition point at which the KVS regime turns to the RKVS one. Zanotti et al (2014) studied, both experimentally and numerically, a pitching airfoil in deep dynamic stall condition. They reported that, during upstroke motion, 3-D numerical models are in better agreement with the experiments as compared to 2-D models.…”
Section: Introductionmentioning
confidence: 99%